Effects of esmolol on hemodynamic responses to laryngoscopy and tracheal intubation in diabetic and non-diabetic patients - Shaik Gulam Osmani; Shaila S Kamath (Wolters Kluwer Medknow Publications, 2014)
Background: The hemodynamic response to laryngoscopy and endotracheal intubation is of concern in diabetic patients. They usually have underlying coronary and cerebrovascular disease which may lead to catastrophes during anesthesia. Materials and Methods: Seventy controlled diabetic and 70 non-diabetic patients were allocated in to four groups. Esmolol 1 mg/kg to study groups and normal saline to control groups was infused slowly over 1 min. Later all patients induced with propofol 2 mg/kg and rocuronium 0.6 mg/kg. SBP, DBP, HR, and SpO 2 recorded every minute after intubation for 10 min. Results: In non-diabetic esmolol (NDE) and diabetic esmolol (DE) group we observed increase in heart rate (HR), systolic blood pressure (SBP), and diastolic blood pressure (DBP), more in DE group compared to NDE group, but was non-significant (P > 0.05). In group non-diabetic control (NDC) and diabetic control (DC) there was significant increase (P = < 0.05) in HR, SBP, DBP for first 2 mins of intubation when compared with base line values. Rise is more marked in DC group than NDC group. Blood glucose measured after 10 mins of intubation shows no significant difference among both groups. Conclusion: Esmolol with low dose fentanyl is a near ideal drug for attenuating pressor response to laryngoscopy and intubation in controlled diabetics.